Event-related potentials (ERPs) and hemodynamic (functional near-infrared spectroscopy, fNIRS) as measures of schizophrenia deficits in emotional behavior - Balconi, Michela; Tirelli, Simone; Frezza, Alessandra (Frontiers in Psychology, 2015)
Recent research evidences supported the significant role of multimethodological neuroscientific approach for the diagnosis and the rehabilitative intervention in Schizophrenia. Indeed both electrophysiological and neuroimaging measures in integration each other appear able to furnish a deep overview of the cognitive and affective behavior in schizophrenia patients. The aim of the present review is focused on the emotional dysfunctional response taking into account the multimeasures for emotional behavior, i.e. the Event-related Potentials (ERPs) and the hemodynamic profile (functional Near-Infrared Spectroscopy, fNIRS). These measures may be considered as predictive measures of the schizophrenia patients’ deficits in emotional behavior. The integration between ERP and fNIRS may support both the prefrontal cortical localization anomaly and the attentional bias toward some specific emotional conditions (mainly negative).